An intelligence diagnostic tool for the diagnostic of hypertension - Soh, Desmond Chuang Kiat (Nanyang Technological University, 2020)
Hypertension (HPY) commonly termed as high blood pressure is a severe health condition where long-term elevated pressure from the blood flow acting against the artery walls. HPY is observed to be a risk factor for health conditions such as heart diseases, cerebrum diseases, and kidney failure, among others. The 24-hour ambulatory blood pressure monitoring (ABPM) is the current gold standard for detection and diagnostic for HPY. White coat HPY and masked HPY (MHPY) are the two classes of HPY that are detected using ABPM. Patients with MHPY, they are observed to have a healthy pressure of the blood in a clinical setting and an elevated pressure of the blood out of the clinical setting. Therefore, making it challenging to identify patients with MHPY, resulting in some remain not treated or not properly treated. Thus, the diagnostic of MHPY using EMD and CNN is proposed in this research work.